1979
DOI: 10.1136/jnnp.42.8.677
|View full text |Cite
|
Sign up to set email alerts
|

Responses of baboon cerebral and extracerebral arteries to prostacyclin and prostaglandin endoperoxide in vitro and in vivo.

Abstract: S U M M A R Y The responses of baboon cerebral and extracerebral arteries to prostaglandin endoperoxide (PGH2) and prostacyclin (PGI2) were investigated on isolated arteries and in vivo by serial angiography. Both PGH2 and PGI2 could produce dose-dependent contraction or relaxation of isolated arteries. PGH2 induced relaxation was indicative of prostacyclin synthetase activity, the enzyme which converts PGH2 to PGI2. In isolated arteries tested one to four hours post mortem only the vertebral artery showed pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1983
1983
1987
1987

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Recent advances in the study of pharmacological properties of arachidonic acid derivatives have provided some clues for a better understanding of the pathophysiology of cerebral arterial constriction following SAH. It has been suggested that an imbalance in the prostacyclin/thromboxane A2 ratio [6,14,19,21], possibly triggered by a free radical reaction initiated by the presence of blood in the subarachnoid spaces [17], might play a major causal role in cerebral vasospasm. However, other factors are also likely to be implicated in the complex pathophysiology of cerebral vasoconstriction and subsequent ischemia following SAH [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in the study of pharmacological properties of arachidonic acid derivatives have provided some clues for a better understanding of the pathophysiology of cerebral arterial constriction following SAH. It has been suggested that an imbalance in the prostacyclin/thromboxane A2 ratio [6,14,19,21], possibly triggered by a free radical reaction initiated by the presence of blood in the subarachnoid spaces [17], might play a major causal role in cerebral vasospasm. However, other factors are also likely to be implicated in the complex pathophysiology of cerebral vasoconstriction and subsequent ischemia following SAH [22].…”
Section: Discussionmentioning
confidence: 99%
“…The doses used in this experiment were about a 1000 fold lower than the doses which have been shown to increase CBF in animals (Jarman et al, 1979;Pickard et al, 1980). The plasma concentrations of PGI2 that were achieved (0.2-0.7 ng'ml; 0.75-1.9 nM) were still about a 100 fold higher than the physiological concentrations which have (Boullin, 1980;Paul et al, 1982).…”
Section: Discussionmentioning
confidence: 85%
“…It is known to be both a potent inhibitor of platelet aggregation (Moncada et al, 1977) and a powerful vasodilator (Armstrong et al, 1978;Szczeklik et al, 1979;Jarman et al, 1979). In vitro experiments with human and baboon cerebral arterial strips have shown that PGI2 produces dose-dependent relaxation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 In human cerebral artery strips it is a more potent constrictor than 5-hydroxytryptamine. 124 Prostacyclin, on the other hand, at low concentrations (-10~8 M) relaxes canine cerebral and basilar arteries, [125][126][127] baboon cerebral 128 and human cerebral, basilar and pial vessels in vitro m - 124 -129 although there is one report describing contractile effects. 130 In pial human vessels prostacyclin strongly antagonises the contractions induced by several vasoactive substances and by cerebrospinal fluid.…”
Section: °mentioning
confidence: 99%